iNKT Cells in Secondary Progressive Multiple Sclerosis Patients Display Pro-inflammatory Profiles - De Biasi, Sara; Simone, Anna Maria; Nasi, Milena; Bianchini, Elena; Ferraro, Diana; Vitetta, Francesca; Gibellini, Lara; Pinti, Marcello; Del Giovane, Cinzia; Sola, Patrizia; Cossarizza, Andrea (Frontiers in Immunology, 2016)
Background. Multiple Sclerosis (MS), an autoimmune disease with neurodegeneration and inflammation, is characterized by several alterations of different T cell subsets. However, few data exist on the role of iNKT lymphocytes. Objective. To identify possible changes in the phenotype of iNKT cells in patients with different clinical forms of MS, and find alterations in their polyfunctionality (i.e., ability to produce simultaneously up to 4 cytokines such as IL-17, TNF-α, IFN-γ, IL-4). Methods. We studied a total of 165 patients, 91 with a Relapsing Remitting form [RR; 31 were treated with interferon (IFN)1-β, 25 with natalizumab (Nat), 29 with glatiramer acetate (Gla); 17 were newly-diagnosed RR without treatment, 19 not active RR without treatment]. Forty-four patients had a Progressive MS: 20 Primary Progressive (PP), 24 Secondary Progressive (SP). A total of 55 age- and sex-matched subjects represented healthy controls (CTR). Among fresh peripheral blood mononuclear cells (PBMC) iNKT cells were identified by flow cytometry. Moreover, the capability of iNKT cells to produce different cytokines (IL-17, TNF-α, IFN-γ, and IL-4) after in vitro stimulation were evaluated in 18 RR (11 treated with Nat and 7 with IFN), 4 PP, 6 SP and 16 CTR. Results. No main differences were found in iNKT cell phenotype among MS patients with different MS forms, or during different treatments. However, the polyfunctional response of iNKT cells showed Th1 and Th17 profiles. This was well evident in patients with secondary progressive form, who are characterized by high levels of inflammation and neurodegeneration, and exhibited a sustained increase in the production of Th17 cytokines. Patients treated with natalizumab displayed lower levels of iNKT cells producing IL-17, TNF-α and IFN-γ. Conclusion. Our data suggest that the progressive phase of the disease is characterized by permanent iNKT activation and a skewing towards an inflammatory phenotype. Compared to other treatments, natalizumab was able to modulate iNKT cell function.